Low carbon effects of super large diameter shield directly cutting piles project: A case study in China - Yifan Chen; Xiangsheng Chen; Jian Ouyang; Xiang Shen; Shuhua Huang; Jian Sheng; Liang Zhang (Case Studies in Construction Materials)
With the increasing number of cutting pile projects in shield tunnel construction, reducing the embedded carbon emissions in cutting pile projects plays a significant role in addressing low-carbon issues. Based on the characteristics of cutting pile projects, this paper defines the carbon emission boundary and proposes a carbon emission calculation model. The model is used to calculate the carbon emissions of cutting pile projects for two different shield tunnel diameters, employing three major construction methods. According to the results, a systematic analysis is conducted on the carbon emission proportions and key influencing factors at each stage of the pile underpinning method. The carbon emissions of three methods and two type of shield diameter were compared. The results show that the material production phase is the primary source of carbon emissions in cutting pile projects using the pile underpinning method (with concrete and steel being the main contributors, accounting for over 90 %), comprising 69.86 % of the total emissions. Compared to the pile underpinning method, the building demolition method can reduce carbon emissions by 54.56 %. Steel segment are a significant influencing factor in carbon emissions for metro shield tunnel cutting pile projects, increasing emissions by 87.46 % and 139.32 % compared to the pile underpinning method and the building demolition method, respectively. These findings provide a reference for selecting construction methods for cutting pile projects from the perspective of carbon emissions.